Whose People? Wales, Israel, Palestine - Jasmine Donahaye (University of Wales Press, 2012)
This monograph is the first to explore the long history of Wales's interest in Palestine and Israel, and its close interest in Jews and Zionism. It examines the relationship that Wales has with the Israel-Palestine situation in the present through a consideration of literary and other published and unpublished material from the nineteenth and twentieth centuries. The work surveys Welsh missionary writing, fictional imaging of Jews, and the political use by Welsh writers of images and ideas about Palestine and Israel. Examining conversionism, semitic discourse, post-colonialism and post-Zionism through a Welsh filter, this monograph contributes to international Jewish studies, to the study of British colonial involvement in Palestine, and to the study of Welsh and Jewish literary and cultural history.